Characteristics of moderate-to-severe chronic pain and its association with daily functional impairment among older outpatients in Vietnam - Thanh Xuan Nguyen; Thu Thi Hoai Nguyen; Huong Thi Thu Nguyen; Tam Ngoc Nguyen; Hong Trang Nguyen; Linh Huyen Vu Ha; Hoa Trung Dinh; Luc Viet Tran; Anh Trung Nguyen; Hoa Lan Nguyen; Robert Joel Goldberg; Janani Thillainadesan; et al. (PLoS ONE, 2025)
Objective(s) To describe the characteristics of moderate-to-severe chronic pain, and its association with daily functional decline among older individuals attending a large outpatient geriatric clinic in Hanoi, Vietnam. Methods A cross-sectional study was undertaken between November, 2019 and March, 2020. In-person structured interviews were conducted in 518 patients 60 years and older with chronic pain. Patient’s self-reported pain was categorised into two levels of mild (0–3), moderate to severe (4–10) pain based on a 0–10 scale. Results The median age of the study sample was 69 years, women accounted for 74.1%. The knee-foot-leg region was the most common site of chronic pain in both groups (39.5% in mild pain vs. 45.1% in moderate-to-severe pain. Participants experiencing moderate-to-severe pain were more likely to describe their pain as dull (65.5%) or burning (11.3%) and to report pain occurring independently of specific activities (48.7%), compared to those with mild pain (53.9%, 1.2%, and 32.4%, respectively). In a multivariable adjusted model, dependency in activities of daily living (OR: 3.73, 95% CI: 1.82–7.68) and dependency in instrumental activities of daily living (OR: 9.41, 95% CI: 3.94–22.5) were significantly associated with moderate-to-severe pain. Conclusions Moderate to severe chronic pain was reported in a high proportion of older Vietnamese outpatients and was associated with impaired daily functional impairment.